The Influence of Community Empowerment Strategies in Environmental Engineering Diarrhea Prevention in the Area of Medan Johor Health Center - Ahmad Jumadin Usman; Ismail Efendy; Asriwati Amirah (Newinera Publisher, 2023)
This research aims to establish the impact that community participation techniques in environmental engineering have on the protection of diarrheal illnesses in the region that is serviced by the Medan Johor Health Center in 2021.An analytical survey with a cross-sectional design was the method of research that was carried out. The total number of individuals included in this research was 2235. This population was sampled using either non-probability sampling or selective sampling, neither of which is based on probability. One hundred different individuals were going to be used as subjects for the research. Univariate, bivariate, and multivariate analyses, in addition to the Chi square test, were utilized in order to analyze the data.According to the findings of the study, the p-value for the advocacy variable was found to be 0.000, while the values for the collaboration and communication variables were 0.001 and 0.002, respectively. This indicates that there is a connection between advocacy, teamwork, communication, and mentorship and the protection of gastroenteritis. The findings of the multivariate analysis revealed that the mentorship variable, which had an OR value of 35,174, was the most important factor in determining the outcomes of this research.Although there is a correlation between advocating, teamwork, communication, and mentorship and the protection of gastroenteritis, the findings of a multivariate analysis indicate that mentoring is the most important component.